1988
DOI: 10.1111/j.1471-0528.1988.tb06816.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal serum levels of relaxin in patients having preterm labour

Abstract: This study is the first report of antenatal levels of relaxin measured by homologous radioimmunoassay in peripheral serum from patients who subsequently had a preterm delivery. Serial blood samples were collected antenatally from a group of subjects known to be at increased risk of preterm labour because of a past history of shortened pregnancy. Serum relaxin was measured using a n homologous radioimmunoassay based o n a synthetic bioactive analogoue of the native hormone. In women whose pregnancies ended pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 4 publications
1
3
0
3
Order By: Relevance
“…Serial blood samples taken during the last weeks of pregnancy showed declining, very low relaxin concentrations in one woman who subsequently had a preterm labour and it was proposed that low relaxin levels caused a decreased suppression on the myomet‐rial activity (MacLennan et al 1986). Another study, however, showed increased values of immunoreactive human relaxin concentration in the 30th week of pregnancy in two of the three women delivered preterm when compared with corresponding values obtained in women delivered at term (Bell et al 1988). Furthermore, women who became pregnant after stimulation with clomiphene citrate, human menopausal gonadotrophin and human chorionic gonadotrophin and subsequent in vitro fertilization have both very high immunoreactive serum relaxin concentrations and a very high frequency of preterm labour (Bell et al 1989).…”
Section: Discussionmentioning
confidence: 70%
“…Serial blood samples taken during the last weeks of pregnancy showed declining, very low relaxin concentrations in one woman who subsequently had a preterm labour and it was proposed that low relaxin levels caused a decreased suppression on the myomet‐rial activity (MacLennan et al 1986). Another study, however, showed increased values of immunoreactive human relaxin concentration in the 30th week of pregnancy in two of the three women delivered preterm when compared with corresponding values obtained in women delivered at term (Bell et al 1988). Furthermore, women who became pregnant after stimulation with clomiphene citrate, human menopausal gonadotrophin and human chorionic gonadotrophin and subsequent in vitro fertilization have both very high immunoreactive serum relaxin concentrations and a very high frequency of preterm labour (Bell et al 1989).…”
Section: Discussionmentioning
confidence: 70%
“…Релаксин представляет собой плейотропный гормон, но основной его биологический эффект заключается в регуляции процессов созревания шейки матки, где он участвует в ремоделировании коллагена путем активации металлопротеиназ [49,50,53]. В ходе многочисленных исследований была показана отрицательная роль повышенного уровня релаксина в отношении развития преждевременных родов [49][50][51][52].…”
Section: оценка сывороточного релаксинаunclassified
“…Eddie, A.R. Lester et al одними из первых показали, что беременные, у которых в дальнейшем происходили преждевременные роды, в течение беременности имели более высокие уровни релаксина в сравнении с теми, которые родили своевременно [49].…”
Section: оценка сывороточного релаксинаunclassified
“…Eddie, A.R. Lester et al совместно с амери-канскими коллегами одними из первых пока-зали, что беременные, у которых в дальнейшем происходили преждевременные роды, в тече-ние беременности имели более высокие уровни релаксина с сравнении с теми, которые родили своевременно [27].…”
Section: релаксин и преждевременные родыunclassified